Beyond Resistant Hypertension: Relationship Between Refractory Hypertension and Obstructive Sleep Apnea. Issue 3 (September 2018) - Martínez-García, Miguel-Angel; Navarro-Soriano, Cristina; Torres, Gerard; Barbé, Ferrán; Caballero-Eraso, Candela; Lloberes, Patricia; Diaz-Cambriles, Teresa; Somoza, María; Masa, Juan F.; González, Mónica; Mañas, Eva; de la Peña, Mónica; et al.
Abstract : Obstructive sleep apnea (OSA) is an independent cause of resistant hypertension (RH) but its association with refractory hypertension (RfH), a recently described form of severe hypertension, has not yet been investigated. This study seeks to analyze the association between the presence and severity of OSA/OSA syndrome with RfH and to compare it with a group of patients with OSA/OSA syndrome and RH. We conducted a multicenter, cross-sectional study of consecutive patients diagnosed with RH by means of 24-hour ambulatory blood pressure monitoring. Those patients with blood pressure levels ≥130/80 mm Hg, despite taking at least 5 antihypertensive drugs, were considered to have true RfH. All patients underwent a sleep study and completed a detailed clinical history related to OSA, current medication, and cardiovascular diseases. Overall, 229 patients were included (mean age, 58.3 years; 63% male), of whom 42 (18.3%) satisfied the criteria for RfH. Compared with those with RH, patients with RfH had a higher cardiovascular risk profile, higher blood pressure measurements, and a 2-fold greater risk of having both severe OSA (odds ratio, 2.1, with a prevalence of apnea-hypopnea index ≥15, 95.2% and apnea-hypopnea index ≥30, 64.3%) and OSA syndrome (apnea-hypopnea index ≥5+Epworth Sleepiness Scale >10; odds ratio, 1.9; 52.4% versus 37.3%; P =0.023), as well as higher OSA severity (apnea-hypopnea index, 41.8 versus 33.8 events/h; P =0.026). Patients with RfH had an even greater prevalence and severity of OSA and OSA syndrome than RH patients, highlighting the need to identify these patients to refer them to sleep units on a preferential basis.